Edukacja, społeczeństwo i praca we wzajemnych międzykulturowych związkach. Przypadek Japonii - Banaszak, Sławomir; Domagalska-Nowak, Karolina; Ratajczak, Łukasz P.; Skowroński, Dariusz; Waszyńska , Katarzyna (Studia Edukacyjne, 2019)
The paper addresses the educational, cultural and economic differences of Japan in relation to Poland as a country representing the values of the Old Continent. In particular, selected aspects of education and parenthood in the Land of the Cherry Blossom were analyzed, as well as partnerships as well as the labor market and organizations. The authors emphasize that their goal is to look for cultural differences, but also for generalizable similarities. Research issues undertaken as part of empirical comparative research focused on the various aspects of social life in both countries are revealed.